Simultaneous evaluation of iris area and subfoveal choroidal thickness in Fuchs uveitis syndrome - Matilde Ruiz-Cruz; Patricia Navarro-López; Gerardo Marcelo Hernández-Valero; Luz Elena Concha-del-Rio (BMC Ophthalmology, 2024)
Abstract Background/aims To simultaneously evaluate iris area (IA) and subfoveal choroidal thickness (SFCT) in eyes with Fuchs Uveitis Syndrome (FUS). Methods We prospectively recruited a case series of patients with FUS at our institution, simultaneously measuring IA with anterior segment spectral domain optical coherence tomography (SD-OCT) and SFCT with enhanced depth imaging optical coherence tomography (EDI-OCT). Iris images were analyzed by ImageJ software. We tested the differences in intereye IA and SFCT with the healthy eye (HE) using the Wilcoxon test, and clinical interpretation was controlled by intraclass correlation coefficient (ICC) between two masked specialists. Results Sixteen patients with unilateral FUS were included. Six were female, and the age range was 37 to 67 (median age 48 years, IQR 41–60). ICC of 98.9%, with a lower confidence interval of 97%. Eyes with FUS had a significant thinning of the total iris median area (p < 0.002), restricted to the temporal and nasal areas compared to the HE (p < 0.01 and < 0.001, respectively). SFCT was also significantly thinner compared to the HE (p < 0.0001). A low correlation was found between iris and choroidal thinning in FUS eyes (rs = 0.21; p = 0.4). Conclusions This study found reduced iris area and subfoveal choroidal thickness in eyes with FUS compared to the normal fellow eye.